Proinflammatory Cytokines in Women with PCOS in Atypical Pathogen Infections - Izabela Chudzicka-Strugała; Iwona Gołębiewska; Grzegorz Brudecki; Wael Elamin; Beata Banaszewska; Marta Chudzicka-Adamczak; Dominik Strugała; Barbara Zwoździak (Diagnostics)
Background/Objectives: Polycystic ovary syndrome (PCOS) is one of the most frequently diagnosed endocrine and metabolic disorders in women of reproductive age before menopause. It is associated with excess androgens and ovarian dysfunction, reduced fertility, the presence of obstetric disorders, but also metabolic disorders, and, among others, insulin resistance, obesity and type II diabetes. Its close relationship with changes in the diversity of the vaginal microbiome, vaginal inflammation and changes in the vaginal microenvironment, which can pave the way for pathogenic microorganisms, is emphasized. Methods: The research in the presented paper focuses on a group of women with PCOS (n = 490) of reproductive age (26–43 years), in whom the frequency of infections of the reproductive system caused by atypical pathogens, Chlamydia trachomatis, Mycoplasma hominis and Ureaplasma spp., were analyzed, and then the immune system response was assessed in terms of the level of serum proinflammatory cytokines, IL-1β, IL-6 and TNF-α. Results: Our results showed a 40% infection rate in the studied group of patients with PCOS, with C. trachomatis being the most common pathogen (17.7%), followed by Ureaplasma spp. (10%) and M. hominis (4.9%). In some cases, co-infections such as Mycoplasma and Ureaplasma were also observed in 3.1% or all three atypical bacteria, M. hominis, Ureaplasma spp. and C. trachomatis, in 4.3% of patients with PCOS. In our study, in women with PCOS and confirmed infection with any atypical pathogen (n = 196), we analyzed the levels of proinflammatory cytokines, IL-1 β a, IL-6 and TNF-α. The results were compared with a control group (control group A) consisting of patients with the same underlying disease, i.e., PCOS (n = 39), who did not experience infection with atypical pathogens or symptoms of gynecological infection. Additionally, a control group B (n = 28) consisting of healthy women (without PCOS and without infection) was introduced. The results regarding the levels of cytokines studied in this work (IL-1β, IL-6, TNF-α) may suggest that the presence of intracellular C. trachomatis in the infection will play a dominant role in the immune system response. In the infections with atypical pathogens analyzed in this study in patients with PCOS, no characteristic clinical features were observed, apart from indications in the form of an increase in the number of leukocytes in the assessment of the vaginal biocenosis, suggesting cervicitis and reported reproductive failure or lower abdominal pain. An additional problem is the inability to detect the presence of atypical pathogens in routine microbiological tests; therefore, confirmation of such etiology requires referral of the patient for targeted tests. Conclusions: Invasion of host cells by atypical pathogens such as C. trachomatis and infections with “genital mycoplasmas” can disrupt the function of these cells and lead to many complications, including infertility. The immune response with the production of proinflammatory cytokines such as TNF-α, IL-1β, and IL-6, observed in response to infection with C. trachomatis, M. hominis, and Ureaplasma spp., induces or amplifies inflammation by activating immune cells or controlling infection, but may lead to the facilitation of the survival of pathogenic microorganisms and irreversible damage to fallopian tube tissues. Especially in the case of the proinflammatory cytosine TNF-α, there seems to be a close correlation with infections with atypical pathogens and a marked immune response, as well as with increased IL-1β and IL-6 values compared with the absence of infection (both in the presence and absence of PCOS). The presented study may suggest the importance of extended diagnostics to include atypical pathogens in the case of PCOS and the importance of research in this area also from the point of view of the immune response.